Distinct infection process of SARS‐CoV‐2 in human bronchial epithelial cell lines. Issue 11 (14th July 2020) - Liao, Yun; Li, Xueqi; Mou, Tangwei; Zhou, Xiaofang; Li, Dandan; Wang, Lichun; Zhang, Ying; Dong, Xingqi; Zheng, Huiwen; Guo, Lei; Liang, Yan; Jiang, Guorun; et al.
Abstract: Coronavirus disease 2019, caused by severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2), leads to a series of clinical symptoms of respiratory and pulmonary inflammatory reactions via unknown pathologic mechanisms related to the viral infection process in tracheal or bronchial epithelial cells. Investigation of this viral infection in the human bronchial epithelial cell line (16HBE) suggests that SARS‐CoV‐2 can enter these cells through interaction between its membrane‐localized S protein with the angiotensin‐converting enzyme 2 molecule on the host cell membrane. Further observation indicates distinct viral replication with a dynamic and moderate increase, whereby viral replication does not lead to a specific cytopathic effect but maintains a continuous release of progeny virions from infected cells. Although messenger RNA expression of various innate immune signaling molecules is altered in the cells, transcription of interferons‐α (IFN‐α), IFN‐β, and IFN‐γ is unchanged. Furthermore, expression of some interleukins (IL) related to inflammatory reactions, such as IL‐6, IL‐2, and IL‐8, is maintained at low levels, whereas that of ILs involved in immune regulation is upregulated. Interestingly, IL‐22, an IL that functions mainly in tissue repair, shows very high expression. Collectively, these data suggest a distinct infection process for this virus in respiratory epithelial cells, which may be linked to its clinicopathological mechanism. Highlights: SARS‐CoV‐2 does not lead to a specific cytopathic effect in 16HBE cells, but maintains continuous release of progeny virions from infected cells. During infection, IL‐22, an interleukin that functions mainly in tissue repair, showed very high expression.